Stranded generation assets: Implications for European capacity mechanisms, energy markets and climate policy - Caldecott, B; McDaniels, J (Smith School of Enterprise and the Environment, 2014)
An increasing number of recently built, high-efficiency combined-cycle gas turbine (CCGT) power plants, are being mothballed or prematurely closed across the European Union as profits from gas are eroded by decreased electricity demand, changing fuel prices and depressed carbon prices. This paper examines how major EU utilities are reacting to the impacts of market and policy factors upon the profitability and value of CCGT assets, how these stranded assets are affecting firm value and strategy, and what implications may exist for energy market design, low-carbon energy and climate policy. Market research and financial information is used to quantify the scale and scope of competitiveness impacts on gas-fired power assets and financial impacts of stranded CCGT assets in terms of asset impairment charges, firm valuation, credit ratings and debt quality. A meta-analysis of developments occurring in 2013 illustrates that stranded CCGT assets are playing an important role in the development and implementation of capacity remuneration mechanisms in different EU member states. We find that governance and policy gaps exist at national and EU levels regarding the appropriate treatment of stranded assets. Careful thinking is required on how the economic costs of stranded assets should be valued in the design and implementation of different capacity policies. Examining the potential competitiveness impacts of different capacity mechanisms and their relationships to stranded assets stands is an important research priority.